A comprehensive approach for the characterization of porous polymers using 13C and 15N dynamic nuclear polarization NMR spectroscopy. Issue 40 (9th October 2020) - Grätz, Sven; de Olivera Junior, Marcos; Gutmann, Torsten; Borchardt, Lars
Abstract : DNP enhanced solid-state NMR techniques are presented as powerful tools to characterize amorphous porous polymers that are of insoluble nature. Abstract : Most porous polymers are notoriously hard to characterize due to their amorphous and completely insoluble nature. On the other hand, they are an interesting class of materials for sorption, catalytic, and electrode applications, thus they warrant in-depth studies. In this contribution, we elaborate on the possibilities that dynamic nuclear polarization offers towards the investigation of the structure of porous polymers. We discuss the advantages and disadvantages of this technique in the investigation of model polymers.